The Cold War : historiography, memory, representation - Jarausch, Konrad 1941- HerausgeberIn; Ostermann, Christian F. 1965- HerausgeberIn; Etges, Andreas 1965- HerausgeberIn; De Gruyter Oldenbourg (De Gruyter Oldenbourg, 2017)
"This volume describes and analyzes the cultural history and representation of the Cold War from an international perspective. That innovative approach focuses on master narratives of the Cold War, places of memory, public and private memorialization, popular culture, and schoolbooks. These general themes are illustrated through a case study of Cold War memory in Berlin, which was a unique former center of Cold War confrontation and competition"--Provided by publisher